Subclinical Hypothyroidism in Children: Natural History and When to Treat - Bona, Gianni (Galenos Publishing, 2013)
Subclinical hypothyroidism (SH) is a quite common disorder in the pediatric age group. The aim of this paper is to present a review of the studies investigating the natural course of SH and the effects of replacement therapy with levothyroxine in childhood. We systematically searched PubMed, Cochrane, and EMBASE (1990 to 2012) and identified 14 articles suitable to be included. SH is a benign process that does not influence anthropometric parameters or puberty onset, and in most cases, it is a remitting disease, with a low risk of development of overt hypothyroidism, more frequently evolving toward euthyroidism or steadily remaining in a condition of isolated hyperthyrotropinemia. Studies analyzing the effects of replacement therapy in SH have reported an increased growth velocity in children with short stature or chronic diseases, discordant effects on thyroid volume reduction, and no effects on neurocognitive function. SH in children and adolescent is often a self-remitting process and its treatment should be considered only when thyroid stimulating hormone values are higher than 10 mIU/L, when clinical signs or symptoms of impaired thyroid function or goiter are detected, or when SH is associated with other chronic diseases. Conflict of interest:None declared.